2010
DOI: 10.1002/cctc.201000136
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight into Gold(I)‐Catalyzed Hydration of Alkynes: Proton Transfer

Abstract: Solvent molecules have a significant impact on the mechanism of the gold(I)‐catalyzed hydration of alkynes as they enable an efficient proton transfer step. As an alternative to such a water‐assisted proton transfer, the counterion can serve as a proton shuttle. However, it seems likely that solvent molecules play a vital role for the overall reaction mechanism in either case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
116
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(124 citation statements)
references
References 25 publications
2
116
1
5
Order By: Relevance
“…However, later studies have clearly shown that intermediate 66 is an artifact of the gas phase and that is quite unlikely in the liquid phase. [96] Moreover, later experimental work has demonstrated that the attack of oxygen [97a-98] and carbon [97b] nucleophiles on the gold-alkyne intermediate occurs preferentially through the opposite face of coordination (anti). In any case, the work by Teles and co-workers opened the door toward gold-catalyzed hydroadditons to alkynes and many of their assumptions are still accepted.…”
Section: A Corma and A Leyva-pørezmentioning
confidence: 99%
“…However, later studies have clearly shown that intermediate 66 is an artifact of the gas phase and that is quite unlikely in the liquid phase. [96] Moreover, later experimental work has demonstrated that the attack of oxygen [97a-98] and carbon [97b] nucleophiles on the gold-alkyne intermediate occurs preferentially through the opposite face of coordination (anti). In any case, the work by Teles and co-workers opened the door toward gold-catalyzed hydroadditons to alkynes and many of their assumptions are still accepted.…”
Section: A Corma and A Leyva-pørezmentioning
confidence: 99%
“…The final step corresponds to the dissociation of [Au(IPr)] + from the enol ether intermediate VI to deliver the transhydroalkoxylated product, 73 with a free energy change of -13.7 kcal/mol, overcoming a relatively high energy barrier of 15.2 kcal/mol via a phenol-assisted pathway, even though this protonation step might be assisted by an acid reagent. 74,75 However, it is also possible that this last step is assisted by the alkyne substrate, being just 6.4 kcal/mol higher in energy than the water-assisted pathway, 76 thus releasing the vinyl ether and regenerating complex I. Given that I and [Au(IPr)(OHR)] + are close in energy, they will be in equilibrium under the reaction conditions.…”
Section: Digold Catalysismentioning
confidence: 99%
“…[38] Thec alculations were performed at DFT level using 6-31G**b asis set for all atoms exceptg oldf or which SDD basis was used. We positioned andc haracterized each transitions tate (TS) using as can procedure leading to ah igh energy structure which was furthermore freely optimized (Supporting Information).…”
mentioning
confidence: 99%